The Egodocumentary Heritage of Sculptor Juozas Kėdainis in the Kupiškis Municipality Public Library - Galvanauskienė, Nida (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] This article analyzes the letters of sculptor Juozas Kėdainis (1915–1998), stored in the Kupiškis Municipality Public Library and which were sent to his family members: from 1933, the letters were addressed to his father Justinas Kėdainis; later, after his father’s death, from 1951 to 1996 – to his brother Bronius Kėdainis. The letters were written from Vilnius, Kaunas, Palanga, Moscow and other cities. The letters of sculptor Juozas Kėdainis are unique in their scope, because they are written during a period of over 60 years – since the 1940s of the independent Lithuania, during the several decades of the Soviet period and up until when the independence of the country was regained. Basing on these letters, the cultural life of that time, relations with close people and love to the native land are all revealed. There is also described the work at the Kaunas Art School and Vilnius State Art Institute (now the Vilnius Academy of Arts). Descriptions of travels, various creative ideas are revealed as well. These letters are not only a multicolored mosaic of Juozas Kėdainis’s life but also a testimony to the Lithuanian way of life in that era.